Post-silking Factor Consequences for N Efficiency Changes Over 38 Years of Commercial Maize Hybrids - Chen, Keru; Vyn, Tony J. (Frontiers in Plant Science, 2017)
Hybrid selection in maize (Zea mays L.) over the decades has increased post-silking dry matter (PostDM) and nitrogen (PostN) accumulation, often with an accompanying increase in one or more N use efficiency (NUE) metrics such as partial factor productivity (PFP), N conversion efficiency (NCE), and N internal efficiency (NIE). More certainty on the underlying mechanisms of how PostDM and PostN changes over time have contributed to NUE gains or losses in modern-era hybrids can only be realized by directly comparing hybrids of different eras in the context of production-system-relevant management systems. A two-year and two-location field study was conducted in Indiana with two N rates (55 and 220 kg N ha-1), three plant densities (54,000, 79,000, and 104,000 plants ha-1) and eight commercial hybrids that were released by a single seed company from 1967 to 2005. The main treatment effects of N rate, density, and hybrid dominated the PostDM and PostN responses, and there were no significant two-way or three-way interactions. Total dry matter at maturity gains averaged 80 kg ha-1 year-1 of hybrid release when averaged over locations, plant densities and N rates. Total N contents at maturity increased 0.68 kg ha-1 year-1, primarily due to annual increases in grain N content (0.8 kg ha-1 year-1). Post-silking N uptake rate increased 0.44 kg ha-1 year-1 for these era hybrids at more favorable production site-years. Gains in average PFP over time were considerably higher at the low N rate (0.9 kg ha-1 year-1) than at the high N rate (0.3 kg kg-1 year-1). The low N rate and higher plant densities also increased relative NIE and NCE values, but without hybrid interactions. Despite considerable genotypic variation, there was no consistent trend of NIE or NCE gains over time in these hybrids primarily because grain and whole-plant N concentrations didn’t decline over the decades at either N rate, and because NIE and NCE were plant-density dependent.